Case Report: Dural Dissection With Ventral Spinal Fluid-Filled Collection in Superficial Siderosis: Insights Into the Pathology From Anterior-Approached Surgical Cases - Yoshii, Toshitaka; Hirai, Takashi; Egawa, Satoru; Hashimoto, Motonori; Matsukura, Yu; Inose, Hiroyuki; Sanjo, Nobuo; Yokota, Takanori; Okawa, Atsushi (Frontiers in Neurology, 2022)
Superficial siderosis (SS) of the central nervous system is a rare disease caused by chronic and repeated hemorrhages in the subarachnoid space. Recently, attention has been paid on the association of SS and dural defect with ventral fluid filled collection in the spinal canal (VFCC). The pathophysiology of hemosiderin deposition in patients with SS and dural defects is still unclear. However, previous studies have suggested the possible mechanism: CSF leaks into the epidural space through the ventral dural defect and repetitive bleeding occurs from the epidural vessels that circulate back to the subarachnoid space through the dural defect, leading to hemosiderin deposition on the surface of the brain, central nerves, and spinal cord. Previously, the surgical closure of dural defect via the posterior approach is reported to be effective in arresting the continued subarachnoid bleeding and disease progression. Herein, we describe SS cases whose dural defects were repaired via the anterior approach. From the direct anterior approach to the ventral dural defect findings, we confirmed that the outer fibrous dura layer is intact, and the defect is localized in the inner thin layer. From the findings of this study, our proposed theory is that dural tear at the inner dural layer causes “dural dissection”, which is likely to occur between the outer fibrous layer and inner dural border cellular layer. Bleeding from the vessels between the inner and outer Line39-40 dural layers seem to be the pathology of SS with dural defect.